Increased Arginase1 expression in tumor microenvironment promotes mammary carcinogenesis via multiple mechanisms. (2nd July 2020) - Croce, Michela; Damonte, Patrizia; Morini, Monica; Pigozzi, Simona; Chiossone, Laura; Vacca, Paola; Bronte, Vincenzo; Barbieri, Ottavia; Astigiano, Simonetta
Abstract: Arginine metabolism plays a significant role in regulating cell function, affecting tumor growth and metastatization. To study the effect of the arginine-catabolizing enzyme Arginase1 (ARG1) on tumor microenvironment, we generated a mouse model of mammary carcinogenesis by crossbreeding a transgenic mouse line overexpressing ARG1 in macrophages (FVB Arg+/+ ) with the MMTV- Neu mouse line (FVB Neu+/+ ). This double transgenic line (FVB Arg+/−;Neu+/+ ) showed a significant shortening in mammary tumor latency, and an increase in the number of mammary nodules. Transfer of tumor cells from FVB Neu+/+ into either FVB wild type or FVB Arg+/+ mice resulted in increase regulatory T cells in the tumor infiltrate, suggestive of an impaired antitumor immune response. However, we also found increased frequency of tumor stem cells in tumors from FVB Arg+/−;Neu+/+ transgenic compared with FVB Neu+/+ mice, suggesting that increased arginine metabolism in mammary tumor microenvironment may supports the cancer stem cells niche. We provide in vivo evidence of a novel, yet unexploited, mechanism through which ARG1 may contribute to tumor development. Abstract : Arginase1, the enzyme catabolizing the amino acid l -arginine, that influences cell proliferation and immune response could be relevant in inducing a tumor microenvironment permissive for cancer development and progression also by the expansion of the cancer stem cells population.